A case of non-classical celiac disease - Peças, Sofia (2019)
Celiac disease is an immune-mediated enteropathy caused by gluten exposure, occurring in genetically susceptible individuals. Although its typical presentation mainly includes gastrointestinal symptoms, non-classical forms are becoming increasingly frequent. In this report, a case of non-classical celiac disease in a seven-year-old child presenting with severe oligoarthralgia is described. With this report, the authors aim to increase awareness of celiac disease and the variability of its presentation as a way to enable a timely diagnosis and treatment, reduce the burden of disease, and improve health-related quality of life.